Evaluating wind energy potential in Pakistan's three provinces, with proposal for integration into national power grid. (January 2016) - Shami, Sajjad Haider; Ahmad, Jameel; Zafar, Raheel; Haris, Muhammad; Bashir, Sajid
Abstract: Pakistan is facing increasing power shortage from the last two decades. The Government of Pakistan (GoP) has taken various remedial measures and is offering incentives for private investment to generate electricity at cheap rates. New hydropower dams were proposed in the past, such as Kalabagh Dam, but could not be commissioned to date. Fossil fuels are depleting and oil has to be imported for oil-fired power plants, which is highly expensive and a burden for the country's economy. This scenario has raised serious concerns among citizens. In this frustrating situation, there is dire need for exploration and installation of alternate renewable energy resources, in particular, wind energy and solar energy to augment the existing power generation and distribution apparatus. These then need to be integrated with the national power grid. Pakistan has enormous wind energy potential, especially in three of its four provinces namely, Khyber Pakhtun Khwa (KPK), Sindh and Balochistan. The country's multifarious terrain includes coastal and hilly areas suitable for installation of large wind turbines. The GoP has taken active steps towards measuring wind speed statistics in various parts of the country. In this paper, the authors analyze wind speed data for the mentioned three provinces. The fourth province, Punjab, has very limited wind energy potential and hence is not considered. Wind speed data for Jiwani (a reference site in Balochistan) was obtained from Pakistan Meteorological Department (PMD) as a case study. The paper attempts to assess how much wind energy can be harnessed from the three provinces. It then focuses on Jiwani whose specific power density is estimated for wind turbine sizing. Lastly, a practical scheme is proposed for integration of wind power output (from windy sites) with the national power grid.